Leveraging Quantum Computing and AI-Driven Integration Platforms for Next-Generation Enterprise Architectures - Himanshu Nigam, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The convergence of quantum computing and artificial intelligence presents transformative opportunities for revolutionizing enterprise architecture (EA). This comprehensive article explores how the integration of quantum computing capabilities with AI-driven platforms addresses the mounting challenges of data complexity and real-time decision-making in modern enterprises. It examines theoretical foundations, practical implementations, and potential impacts of hybrid quantum-classical systems on next-generation enterprise architectures. By investigating quantum advantages in computing, AI-driven integration platforms, and self-healing architectures, this article provides insights into the technical requirements and implementation challenges organizations face. Through experimental use cases in financial services and supply chain management, the article demonstrates the practical applications and benefits of quantum-AI integration. It highlights the importance of developing robust frameworks for adopting these cutting-edge technologies, paving the way for resilient and innovative enterprise architectures that can effectively respond to the demands of an increasingly interconnected digital landscape.
Keywords: Enterprise Architecture Transformation; Quantum-AI Integration; Self-Healing Systems; Hybrid Computing Infrastructure; Next-Generation Decision Making